Predictive value of quad serum markers for adverse pregnancy outcome in antiphospholipid antibody syndrome. (May 2021) - Hong, Sir-Yeon; Kim, Seo-Yeon; Kim, Jin-Ha; Hong, Jee-Youn; Sung, Ji-Hee; Choi, Suk-Joo; Oh, Soo-Young; Roh, Cheong-Rae
Purpose: We investigated the validity of quad serum markers for the prediction of adverse pregnancy outcome (APO) in women with antiphospholipid antibody syndrome (APS). Methods: We included 75 women with APS delivered at our institution. APO was defined as stillbirth, small for gestational age (SGA), severe preeclampsia, or preterm delivery. First, we compared clinical characteristics between patients with or without composite APO. Second, we compared the rate of APO according to abnormal level of quad serum markers. Lastly, receiver operating characteristic (ROC) curve analysis was performed. Results: APS mothers with APO showed higher median α-fetoprotein (AFP) and inhibin A compared with those without APO. They were also associated with higher rates of positive risk of Down syndrome and neural tube defect. Elevated AFP, human chorionic gonadotropin (hCG), and inhibin A level was associated with higher rates of stillbirth, SGA, preterm delivery, and composite APO. ROC curve for prediction of stillbirth revealed an area under the curve of 0.835 for AFP, 0.781 for hCG, and 0.932 for inhibin A. For composite APO, the area under the ROC curve was 0.692 for AFP and 0.810 for inhibin A. Conclusion: Elevated AFP, hCG, and inhibin A in women with APS demonstrated a high predictive value for APO, especially stillbirth.